Psychische Komorbiditäten bei alkoholbedingten Störungen = Mental comorbidities of alcohol-related disorders - Preuss, Ulrich W.; Mann, Karl (Der Nervenarzt, 2016)
SummaryBackgroundAlcohol-related disorders have a high comorbidity with mental disorders and vice versa, alcohol consumption plays an important role in affective disorders and schizophrenic psychoses. In developing the current S3 guidelines evidence-based knowledge on the rate and significance of comorbid disorders in alcohol use disorders has been compiled to generate recommendations for treatment.Methods In preparation for the guidelines, previous international guidelines and a systematic literature search were taken into consideration. Recommendations for various and specific clinical situations were derived from these sources based on evidence grading. Evidence and recommendations were subdivided into psychotherapy, pharmacotherapy and combination therapy, each having differential efficacies in the treatment of psychiatric symptoms and alcohol consumption behavior. Furthermore, a separate treatment pathway was developed for a stepwise approach to affective disorders for both comorbidities.ConclusionAppearing for the first time in guidelines are specific treatment recommendations for comorbid mental diseases in alcohol use disorders. These recommendations extend to different treatment approaches including diagnostics and settings, affording clinicians more pragmatic relevance.